Alveolar Rhabdomyosarcoma of Nasopharynx and Paranasal Sinuses in Children Diagnosis and Treatment—Review of the Literature and Case Report - Cristian Mârțu; Ștefan Dragoș Tîrnovanu; Ioana Mârțu; Dan Ferariu; Dan Mârțu; Alexandra Jităreanu; Luminița Rădulescu (Medicina)
Alveolar rhabdomyosarcoma (aRMS) is a rare pediatric malignant tumor with a poor prognosis, particularly when located in the rhinopharynx and sphenoidal floor, which complicates diagnosis and increases the risk of misclassification as benign growths. The specific genotype of aRMS is associated with a worse clinical outcome. In young children, especially those aged 4 to 12 years, rhinopharyngeal masses are often attributed to chronic adenoiditis; however, other benign (e.g., angiofibroma in boys) and malignant tumors may also be present. Initial symptoms frequently include nasal obstruction, muco-purulent nasal discharge, serous otitis media, sinusitis, and epistaxis. Rhabdomyosarcoma is the second most common ENT neoplasm in children, following lymphoma, with an incidence of approximately 6 cases per 1,000,000 annually. This report presents the case of an 8-year-old boy diagnosed with aRMS, accompanied by a literature review. Alveolar rhabdomyosarcoma should be suspected in children presenting with a vegetative tumor in the rhinopharynx or paranasal sinuses. Combined treatment approaches (surgery, radiotherapy, and chemotherapy) should be tailored to tumor characteristics. Neuronavigation-guided functional endoscopic sinus surgery (FESS) is an effective option for achieving complete tumor excision, depending on tumor size and extent. The prognosis remains reserved and is contingent upon accurate evaluation and timely intervention. Rigorous follow-up, including endoscopic and imagistic investigation, is crucial for early detection of recurrences, thereby improving treatment outcomes.